Penerapan Algoritma Ascent Hill Climbing Pada Game Edukasi Penyusunan Deretan Angka Puzzle-8 - Mike Febri Mayang Sari (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
Number preparation using Puzzle 8 is a game that is very popular with children at this time, this educational game has very broad benefits for improving memory and thinking patterns. The 8 Puzzle Game Algorithm must have a clear step-by-step process in order to achieve a goal in the Search system. Logic Game 8 puzzles using the Ascent Hill Climbing Algorithm are often used in artificial intelligence. The problem that occurs in the research, the lack of understanding of children to find a suitable algorithm to arrange the 8 Puzzle game according to the principle of how an algorithm works. The game of compiling 8 puzzles must follow the rules that have been determined in order to obtain the correct algorithm so as to produce an arrangement that is in accordance with the initial data. The benefit of this research is that it provides a solution to complete the game of 8 puzzles according to the rules of the Ascent Hill Climbing Search Algorithm so as to produce a solution in the search method. Based on the search process, the final result of the puzzle game is in the correct position of 8 squares according to the initial rule, so the search is stopped and produces a goal.